Pathways linked to unresolved inflammation and airway remodelling characterize the transcriptome in two independent severe asthma cohorts - Sanchez-Ovando,S; Pavlidis,S; Kermani,NZ; Baines,KJ; Barker,D; Gibson,PG; Wood,LG; Adcock,IM; Chung,KF; Simpson,JL; Wark,PAB (Respirology, 2022)
Background and objectiveSevere asthma (SA) is a heterogeneous disease. Transcriptomic analysis contributes to the understanding of pathogenesis necessary for developing new therapies. We sought to identify and validate mechanistic pathways of SA across two independent cohorts.MethodsTranscriptomic profiles from U-BIOPRED and Australian NOVocastrian Asthma cohorts were examined and grouped into SA, mild/moderate asthma (MMA) and healthy controls (HCs). Differentially expressed genes (DEGs), canonical pathways and gene sets were identified as central to SA mechanisms if they were significant across both cohorts in either endobronchial biopsies or induced sputum.ResultsThirty-six DEGs and four pathways were shared across cohorts linking to tissue remodelling/repair in biopsies of SA patients, including SUMOylation, NRF2 pathway and oxidative stress pathways. MMA presented a similar profile to HCs. Induced sputum demonstrated IL18R1 as a shared DEG in SA compared with healthy subjects. We identified enrichment of gene sets related to corticosteroid treatment; immune-related mechanisms; activation of CD4+ T cells, mast cells and IL18R1; and airway remodelling in SA.ConclusionOur results identified differentially expressed pathways that highlight the role of CD4+ T cells, mast cells and pathways linked to ongoing airway remodelling, such as IL18R1, SUMOylation and NRF2 pathways, as likely active mechanisms in the pathogenesis of SA.